Post-traumatic growth following acquired brain injury: a systematic review and meta-analysis - Kinsella, Elaine L.; Grace, Jenny J.; Muldoon, Orla T.; Fortune, Donal G. (Frontiers in Psychology, 2015)
The idea that acquired brain injury (ABI) caused by stroke, haemorrhage, infection or traumatic insult to the brain can result in posttraumatic growth (PTG) for individuals is increasingly attracting psychological attention. However PTG also attracts controversy as a result of ambiguous empirical findings. The extent that demographic variables, injury factors, subjective beliefs, and psychological health are associated with PTG following ABI is not clear. Consequently, this systematic review and meta-analysis explores the correlates of variables within these four broad areas and PTG. From a total of 744 published studies addressing PTG in people with ABI, eight studies met inclusion criteria for detailed examination. Meta-analysis of these studies indicated that growth was related to employment, longer education, subjective beliefs about change post-injury, relationship status, older age, longer time since injury, and lower levels of depression. Results from homogeneity analyses indicated significant inter-study heterogeneity across variables. There is general support for the idea that people with ABI can experience growth, and that various demographics, injury-related variables, subjective beliefs and psychological health are related to growth. The contribution of social integration and the forming of new identities post-ABI to the experience of PTG is explored. These meta-analytic findings are however constrained by methodological limitations prevalent in the literature. Clinical and research implications are discussed with specific reference to community and collective factors that enable PTG.